Carbon Deposition during CO2 Electrolysis in Ni-Based Solid-Oxide-Cell Electrodes. (2nd June 2015) - Skafte, Theis Løye; Graves, Christopher; Blennow, Peter; Hjelm, Johan
Abstract : The carbon formation threshold in an operating cell was investigated during electrolysis of an idealized reactant atmosphere of CO and CO2 . The electrolysis current was gradually increased in steps until the cell voltage spontaneously increased, thereby indicating cell degradation and possibly the onset of carbon deposition. The outlet gas composition at each current step was estimated based on the inlet gas composition and the reactant conversion using Faraday's law. The increase in voltage was observed at lower outlet pCO/pCO2 ratios than that corresponding to the expected thermodynamic threshold for carbon formation. The degradation observed was related to the fuel electrode, as confirmed by electrochemical impedance spectroscopy. Mitigation of the degradation mechanism was attempted by infiltrating gadolinium doped ceria. The onset of carbon deposition was largely unaffected, but the polarization resistance of the electrode during electrolysis was significantly decreased.